Mental health and suicide in former professional soccer players. Issue 12 (21st July 2020) - Russell, Emma R; McCabe, Thomas; Mackay, Daniel F; Stewart, Katy; MacLean, John A; Pell, Jill P; Stewart, William
Abstract : Introduction: There is growing recognition of an association between contact sports participation and increased risk of neurodegenerative disease, including Alzheimer's disease and chronic traumatic encephalopathy. In addition to cognitive impairment, a range of mental health disorders and suicidality are proposed as diagnostic features of traumatic encephalopathy syndrome, the putative clinical syndrome associated with chronic traumatic encephalopathy. However, to date, epidemiological data on contact sport participation and mental health outcomes are limited. Methods: For a cohort of former professional soccer players (n=7676) with known high neurodegenerative mortality and their matched general population controls (n=23 028), data on mental health outcomes were obtained by individual-level record linkage to national electronic records of hospital admissions and death certification. Results: Compared with matched population controls, former professional soccer players showed lower risk of hospital admission for anxiety and stress related disorders, depression, drug use disorders, alcohol use disorders and bipolar and affective mood disorders. Among soccer players, there was no significant difference in risk of hospitalisation for mental health disorders between outfield players and goalkeepers. There was no significant difference in rate of death by suicide between soccer players and controls. Conclusions: Among a population of former professional soccer players with known high neurodegenerative disease mortality, hospital admissions for common mental health disorders were lower than population controls, with no difference in suicide. Our data provide support for the reappraisal of currently proposed diagnostic clinical criteria for traumatic encephalopathy syndrome, in particular the inclusion of mental health outcomes.